Viral hepatitis B epidemiology in Sakha republic (Yakutia) - S. I. Semenov; R. G. Savvin; S. G. Nikitina; S. S. Maksimova; V. G. Krivoshapkin; S. S. Sleptsova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate epidemiologic state on viral hepatitis B in Sakha republic (Yakutia).Material and methods. Data of the Russian Federal Service for Surveillance on Consumer Rights Protection and Human Wellbeing (Rospotrebnadzor) for Sakha republic (report form #1) and results of enzyme-linked immunoassay (EIA) for viral hepatitis markers (HBsAg, a-HBcor IgG, a-HDV, a-HCV) in population of 17 areas of republic were utilized.Results. In investigated region morbidity due to both acute and chronic forms of hepatitis B has a tendency to decrease. According to EIA results the prevalence of hepatitis B virus infection markers in population corresponds to criteria of intermediate intensity and for hepatitis D virus — to high intensity.Conclusions. Morbidity due to hepatitis is significantly higher: i.e. 5 times over that for the Russian Federation in general.